TOTAL PHENOLIC CONTENTS AND ANTIOXIDANT ACTIVITIES OF TEN SOYBEAN PROMISING LINES TOLERANT TO ACID SOIL - Heru Kuswantoro, Eriyanto Yusnawan, Alfi Inayati & (Proceeding of International Congress, 2014)
Marginal land such as acid soil has been recently used to cultivate soybean since soybean cultivated areain Java has shifted to other valuable crops. This expansion aims to fulfill national soybean demand and toreduce soybean import as well as to ensure soybean security. Ten soybean promising lines tolerant to acidsoil have been bred to address this issue. Secondary metabolites in soybean, i.e. phenolic compounds varyin each genotype. These compounds function mainly as chemical defense against insects and pathogens.Also, the phenolic compounds including flavonoids which hypothetically have antioxidant activities havepositive effects to human health. Phenolic contents of ten soybean promising lines ranged from 2.87 to3.73 mg GAE/g. Five varieties, i.e. Wilis, Tanggamus, Anjasmoro, Grobogan, and Argomulyo as the checkshad the phenolic contents of 3.02 to 3.93 mg GAE/g. Flavonoid contents of the ten lines varied from 0.57to 0.76 mg CAE/g. There were no check varieties which had the flavonoid contents higher than those ofthe promising lines. The Tgm/Anjâ784, Tgm/Anjâ856, Tgm/Anjâ844, and Tgm/Anjâ857 had the equallyhigh flavonoid contents, i.e. 0.76, 0.75, 0.72, and 0.72 mg CAE/g, respectively. Antioxidant activities as indicatedby DPPH values of the ten soybean lines were lower than those of Wilis, Argomulyo, andGrobogan.Keywords: soybean promising line, acid soil, phenolic content, flavonoid content, antioxidant activity.